Cognitive Improved LEACH (CogILEACH) Protocol for Wireless Sensor Network - Rahman, Md Mahbubur; Miah, Md Sipon; Sharmin, Dilruba (Discoveries in Agriculture and Food Sciences, 2016)
In this paper, we proposed the Cognitive Improved Low Energy Adaptive Clustering Hierarchy (CogILEACH) protocol that is the spectrum aware extension of the Low Energy Adaptive Clustering Hierarchy (LEACH) protocol. In CogILEACH, which selects a cluster head (CH) based on its ratio between the current residual energy and an initial energy, and multiplies by the root square of its number of neighbor nodes. The simulation results show that CogILEACH protocol improves the lifetime of the network compared to both the LEACH protocol and ILEACH protocol under two-level homogeneity.